Is intervertebral disc pressure linked to herniation?: An in-vitro study using a porcine model. Issue 9 (14th June 2016) - Noguchi, Mamiko; Gooyers, Chad E.; Karakolis, Thomas; Noguchi, Kimihiro; Callaghan, Jack P.
Abstract: Approximately 40% of low back pain cases have been attributed to internal disc disruption. This disruption mechanism may be linked to intradiscal pressure changes, since mechanical loading directly affects the pressure and the stresses that the inner annulus fibrosus experiences. The objective of this study was to characterize cycle-varying changes in four dependent measures (intradiscal pressure, flexion–extension moments, specimen height loss, and specimen rotation angle) using a cyclic flexion–extension (CFE) loading protocol known to induce internal disc disruption. A novel bore-screw pressure sensor system was used to instrument 14 porcine functional spinal units. The CFE loading protocol consisted of 3600 cycles of flexion–extension range of motion (average 18.30 (SD 3.76) degrees) at 1 Hz with 1500 N of compressive load. On average, intradiscal pressure and specimen height decreased by 47% and 62%, respectively, and peak moments increased by 102%. From 900 to 2100 cycles, all variables exhibited significant changes between successive time points, except for the specimen posture at maximum pressure, which demonstrated a significant shift towards flexion limit after 2700 cycles. There were no further changes in pressure range after 2100 cycles, whereas peak moments and height loss were significantly different from prior time points throughout the CFE protocol. Twelve of the 14 specimens showed partial herniation; however, injury type was not significantly correlated to any of the dependent measures. Although change in pressure was not predictive of damage type, the increase in pressure range seen during this protocol supports the premise that repetitive combined loading (i.e., radial compression, tension and shear) imposes damage to the inner annulus fibrosus, and its failure mechanism may be linked to fatigue.